Eutetrarhynchid trypanorhynchs (Cestoda) from elasmobranchs off Argentina, including the description of Dollfusiella taminii sp. n. and Parachristianella damiani sp. n., and amended description of Dollfusiella vooremi (São Clemente et Gomes, 1989) - Menoret, Adriana (2014)
During a parasitological survey of teleosts and elasmobranchs in the Argentine Sea, 3 species of eutetrarhynchids were collected from the batoids Myliobatis goodei Garman and Psammobatis bergi Marini, and the shark Mustelus schmitti Springer. The specimens collected from Mu. schmitti were identified as Dollfusiela vooremi (São Clemente et Gomes, 1989), whereas the specimens from My. goodei and Ps. bergi resulted in new species of Dollfusiella Campbell et Beveridge, 1994 and Parachristianella Dollfus, 1946, respectively. Dollfusiella taminii sp. n. from Ps. bergi is characterised by a distinct basal armature with basal swelling and a heteroacanthous homeomorphous metabasal armature with 7–9 falcate hooks per principal row. Parachristianella damiani sp. n. from My. goodei lacks a distinct basal armature, having 2–3 initial rows of uncinate hooks, a heteroacanthous heteromorphous metabasal armature with the first principal row of small hooks, followed by rows with 10–14 large hooks. This is the first record of Parachristianella in the southwestern Atlantic. The amended description of D. vooremi includes the detailed description of the tentacular armature, including SEM micrographs of all tentacular surfaces. This species is characterised by a basal armature consisting of rows of uncinate and falcate hooks, a basal swelling and a metabasal armature with billhooks on the antibothrial surface and uncinate hooks on the bothrial surface. The scolex peduncle of D. vooremi is covered with enlarged spinitriches. This species is restricted to carcharhiniform sharks, since the report of D. vooremi in Sympterygia bonapartii Müller et Henle off Bahía Blanca (Argentina) is dubious.